Meat quality of indigenous fat-tail Namaqua Afrikaner, Dorper and the South African Mutton Merino breeds - Burger, Alta (Stellenbosch : Stellenbosch University, 2015)
Thesis (M Social Work)--Stellenbosch University, 2015.